Defining the security policy and architectural design of managing documents using RCBS model - Solamo, Ma. Rowena C. (2006., 2006)
One of the most important information that the College of Engineering, University of the Philippines, Diliman should maintain are the grades of its students. Their security and management will depend on specific documents or forms being signed and processed, and the roles that individual users play within the system. Currently, they have an enormous number of student records and documents or forms to maintain, and all of their processes are manually done. Even with the five (5) College Administration Staff (CAS) who are tasked to maintain the grades, it is very tedious and time consuming to handle even one student record or process a single document. This research takes a look at digital signatures, public key infrastructures, and current access control security models that can be used to define the security that will ensure the authenticity, confidentiality and integrity of the grades of the College's student to facilitate the future computerization of the grades record system.
Thesis (M.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Digital signatures; Computer security; Public key infrastructure (Computer security).